Dynamic Stereoselection of Peptide Helicates and Their Selective Labeling of DNA Replication Foci in Cells. Issue 16 (28th January 2021) - Gómez‐González, Jacobo; Pérez, Yolanda; Sciortino, Giuseppe; Roldan‐Martín, Lorena; Martínez‐Costas, José; Maréchal, Jean‐Didier; Alfonso, Ignacio; Vázquez López, Miguel; Vázquez, M. Eugenio
Abstract: Although largely overlooked in peptide engineering, coordination chemistry offers a new set of interactions that opens unexplored design opportunities for developing complex molecular structures. In this context, we report new artificial peptide ligands that fold into chiral helicates in the presence of labile metal ions such as Fe II and Co II . Heterochiral β‐turn‐promoting sequences encode the stereoselective folding of the peptide ligands and define the physicochemical properties of their corresponding metal complexes. Circular dichroism and NMR spectroscopy in combination with computational methods allowed us to identify and determine the structure of two isochiral ΛΛ‐helicates, folded as topological isomers. Finally, in addition to the in‐vitro characterization of their selective binding to DNA three‐way junctions, cell‐microscopy experiments demonstrated that a rhodamine‐labeled Fe II helicate was internalized and selectively stains DNA replication factories in functional cells. Abstract : Artificial bipyridine‐containing peptide ligands encode in their sequence the stereoselective folding into chiral three‐stranded Fe II or Co II peptide helicates and as kinetically inert dinuclear Co III complexes by in‐situ oxidation. These peptide helicates selectively label DNA replication foci in functional cells.